BODY, CULTURE AND MOVEMENT: REFLECTIONS ON HUMAN MOTRICITY IN A PHENOMENOLOGICAL PERSPECTIVE - Leite, Francinaldo Freitas (2018)
The Science of Human Motricity contemplates the dynamics of school physical education, sports and cultural manifestations, seeking to solve ontological, epistemological and political problems, becoming valid from the theoretical and methodological presuppositions of phenomenology, through the senses exposed through the intentional human movement. In this research, we had the main objective of identifying and interpreting meanings of the participation in the activities of the human motricity, from what is perceived by its own practitioners. The research instruments were: observation and interview, as qualitative techniques for obtaining data. Participants included 35 practitioners of human motive activities, including handball players, cyclists, caratecas, capoeiristas and dancers of gangs. The results showed that there is an approximation of meanings for the participants of motor manifestations, and the emotional content is perceived as the sense of being a practitioner of these activities.